THE INFLUENCE OF MERONCE EDUCATIONAL GAME ON MOTOR DEVELOPMENT IN LEARNING COLORS - Nurjannah Nurjannah; Nurdiana Nurdiana (Jurnal Real Riset, 2023)
This motor development is caused by several things, including habits in the limbs that allow students to be able to move places, genetics, psychological aspects, and muscle tone abnormalities or neuromuscular diseases. This research was a quasi-experimental with One Group Pretest-Posttest design. The sample was 15 students. The results of the study found that the majority of children in the preschool age group before being given the Meronce Educational Game was in the category of starting to develop as many as 7 respondents (46.7%). The fine motor development of students after being given the Meronce Educational Game was mostly in the category as expected as many as 8 respondents (53.3%). There is an effect of Meronce's Educational Game on Fine Motor Development of students, the significance value is = 0.000 where 0.05. It is hoped that studets will improve their fine motor development through books and other information.Keywords : Meronce, Educational Game, Motor Development